Solid oxide fuel cell and preparation method thereof
Through step-by-step sintering and co-precipitation methods, the problem of complex preparation of electrolyte-supported solid oxide fuel cells and uneven mixing of anode materials is solved, and efficient and low-cost battery preparation is achieved, which improves electrochemical performance and stability.
Patent Information
- Application Number
- CN202411450106.1
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-10-17
- Publication Date
- 2025-01-14
AI Technical Summary
The existing electrolyte-supported solid oxide fuel cells have complex preparation methods and many process procedures, resulting in long production cycles, high costs, difficult to control porosity, and uneven mixing of anode material components.
The step-by-step sintering process is used to simplify the sintering process, and the composite oxide anode powder is prepared by co-precipitation method. The rare earth elements are completely dissolved in YSZ to achieve uniform mixing of the anode material components, and the thermal stress and microstructure changes are regulated through multi-stage sintering. , reduce the risk of warpage and crushing.
The preparation cycle is shortened, the production cost is reduced, the reactive site and electrochemical performance of the battery are improved, the uniform mixing of the anode material and the reduction of particle size are achieved, and the stability and efficiency of the battery are enhanced.
Smart Images

Figure CN119315068A_ABST
Abstract
Description
Technical Field
[0001] The present invention relates to the technical field of solid oxide fuel cells, and in particular to a solid oxide fuel cell and a preparation method thereof. Background Art
[0002] At present, solid oxide fuel cells (SOFCs) are a branch of the fuel cell field. Their main function is to provide a reaction site for converting the chemical energy of fuel into electrical energy. Due to their unique structure and working characteristics, they have the advantages of high power generation efficiency, wide range of fuels, low material cost, long service life, high waste heat utilization value, flexible and convenient installation, and low emissions. Ni-yttria-stabilized zirconia (Ni-YSZ) anode is the most classic SOFC anode material in the prior art. Among them, yttria-stabilized zirconia (YSZ) is a carrier of Ni, which can better adjust the thermal expansion coefficient between the anode and the electrolyte. At the same time, metal Ni can conduct electrons and catalyze the oxidation of hydrogen molecules.
[0003] At present, according to the support body, solid oxide fuel cells can be divided into three types, namely, anode-supported type, electrolyte-supported type and cathode-supported type. Among them, electrolyte-supported solid oxide fuel cells have attracted widespread attention due to their good resistance to redox and thermal cycling.
[0004] However, in the prior art, the preparation methods of electrolyte-supported solid oxide fuel cells mainly have the following problems: the tape casting method mainly prepares the support body green body by tape casting, and combines them together after lamination by warm isostatic pressing. The specific process is: use the anode slurry to tape cast the green body, laminate it with the electrolyte, combine it together by warm isostatic pressing, and then sinter it into a half-cell, and finally print the barrier layer, sinter and print the cathode, sinter to prepare the full cell, or directly print the cathode and sinter to prepare the full cell. The tape-casting process itself has high requirements on the fluidity of the slurry. The slurry used for tape-casting contains a high content of other reagents (such as binders, dispersants and other additives, as well as water) in addition to ceramic powder, which leads to high shrinkage rate of the green body during drying and firing, and easy cracking. In particular, the preparation process is complicated, requires many process procedures, and has a long production cycle, which brings many inconveniences to production. The sol-gel method requires a long time to prepare raw materials, has high costs, is difficult to control porosity and distribution, and has limited reliability, which is prone to performance differences between batches. Other existing methods also have some problems such as limiting sample size and shape, and difficulty in controlling porosity and distribution, especially due to the long production cycle.
[0005] Therefore, how to provide a method for preparing an electrolyte-supported solid oxide fuel cell with a short process and high efficiency, and how to achieve uniform mixing of the components of the anode material are technical problems to be solved urgently in the present invention. Summary of the invention
[0006] In order to solve the above technical problems, the present invention provides a solid oxide fuel cell and a preparation method thereof. Through step-by-step sintering, the sintering process is simplified, the debinding process is optimized, the sintering time is shortened, and the warping of the electrolyte-supported solid oxide fuel cell is reduced, thereby solving the problem of easy breakage during the test process. At the same time, a composite oxide anode powder with uniform composition is prepared by co-precipitation, and the doped rare earth elements can be completely dissolved in YSZ, thereby achieving uniform mixing of the components in the composite oxide anode powder. The particles prepared by the co-precipitation method have a smaller particle size, thereby reducing the subsequent grinding intensity.
[0007] To achieve this object, the present invention adopts the following technical solutions:
[0008] In a first aspect, the present invention provides a method for preparing a solid oxide fuel cell, the method comprising the following steps:
[0009] Applying a first electrode slurry to one side of the electrolyte substrate, sintering once to obtain an electrode half-cell, applying a second electrode slurry to the other side of the electrolyte substrate in the electrode half-cell, sintering twice to obtain a solid oxide fuel cell;
[0010] Wherein, the first electrode slurry includes anode slurry, and the second electrode slurry includes cathode slurry;
[0011] Alternatively, the first electrode slurry comprises a cathode slurry, and the second electrode slurry comprises an anode slurry.
[0012] It should be noted that the electrolyte substrate used in the present invention can be purchased or prepared using existing techniques.
[0013] In the preparation process of the solid oxide fuel cell of the present invention, the coating order of the cathode slurry and the anode slurry is not limited. The anode slurry can be first coated on the surface of one side of the electrolyte substrate to obtain an anode half-cell, and then the cathode slurry is coated on the other side to obtain a solid oxide fuel cell; or the cathode slurry can be first coated on the surface of one side of the electrolyte substrate to obtain a cathode half-cell, and then the anode slurry is coated on the other side to obtain a solid oxide fuel cell.
[0014] The present invention combines step-by-step coating and stepped sintering, simplifies the existing solid oxide fuel cell sintering process, optimizes the debinding process, thereby shortening the sintering time, and improves the problems of excessive local thermal stress and battery warping caused by the mismatch of thermal physical properties between materials in the electrolyte-supported solid oxide fuel cell. The bonding force between the materials in the battery is good, and the materials are not easy to break during the test process. The preparation process of the present invention greatly shortens the preparation cycle, avoids complex process procedures such as tape casting that have high requirements on preparation conditions, has low production costs, many battery reaction active sites, and better electrochemical performance.
[0015] As a preferred technical solution of the present invention, the primary sintering and the secondary sintering each independently include a first stage sintering, a second stage sintering, a third stage sintering and a fourth stage sintering.
[0016] The present invention adopts four-stage sintering. The first stage of sintering is carried out under low temperature conditions, which can disperse the binder components in the anode slurry or cathode slurry to the greatest extent, reduce the influence of the binder on the material, and fully remove the impurities and bubbles contained therein; the purpose of the second stage of sintering is to remove the pore-forming medium and leave a pore structure in situ at the position of the pore-forming agent to form a pore structure; the third stage of sintering can rearrange the particles and promote crystallization; the fourth stage of sintering is a process of grain growth, thereby forming stable anode and cathode phases. The present invention gradually increases the temperature through step-by-step sintering, gradually regulates the microstructural changes of the anode and cathode pole pieces, and controls the distribution of thermal stress, thereby increasing the flatness of the battery, improving the warping phenomenon, and ensuring the stability of the battery structure.
[0017] As a preferred technical solution of the present invention, the temperature of the first sintering stage is 150-300°C, for example, 150°C, 180°C, 200°C, 220°C, 250°C, 280°C or 300°C.
[0018] Preferably, the heating rate of the first sintering stage is 0.2-1°C / min, for example, 0.2°C / min, 0.3°C / min, 0.4°C / min, 0.5°C / min, 0.6°C / min, 0.7°C / min, 0.8°C / min, 0.9°C / min or 1°C / min.
[0019] Preferably, the holding time of the first stage sintering is 60 to 120 min, for example, 60 min, 70 min, 80 min, 90 min, 100 min, 110 min or 120 min.
[0020] Preferably, the temperature of the second sintering stage is 400-600°C, for example, 400°C, 420°C, 440°C, 460°C, 480°C, 500°C, 520°C, 540°C, 560°C, 580°C or 600°C.
[0021] Preferably, the heating rate of the second sintering stage is 0.8-2°C / min, for example, 0.8°C / min, 0.9°C / min, 1°C / min, 1.1°C / min, 1.2°C / min, 1.3°C / min, 1.4°C / min, 1.5°C / min, 1.6°C / min, 1.7°C / min, 1.8°C / min, 1.9°C / min or 2°C / min, etc.
[0022] Preferably, the holding time of the second sintering stage is 120 to 240 min, for example, 120 min, 140 min, 160 min, 180 min, 200 min, 220 min, 240 min, etc.
[0023] Preferably, the temperature of the third sintering stage is 800-950°C, for example, 800°C, 820°C, 850°C, 880°C, 900°C, 920°C or 950°C.
[0024] Preferably, the heating rate of the third sintering stage is 1-2°C / min, for example, 1°C / min, 1.1°C / min, 1.2°C / min, 1.3°C / min, 1.4°C / min, 1.5°C / min, 1.6°C / min, 1.7°C / min, 1.8°C / min, 1.9°C / min or 2°C / min, etc.
[0025] Preferably, the holding time of the third stage sintering is 120 to 240 min, for example, 120 min, 140 min, 160 min, 180 min, 200 min, 220 min, 240 min, etc.
[0026] Preferably, if the surface of the electrolyte substrate is coated with the anode slurry, the temperature of the fourth sintering stage is 1250-1350°C, for example, 1250°C, 1260°C, 1270°C, 1280°C, 1290°C, 1300°C, 1310°C, 1320°C, 1330°C, 1340°C or 1350°C, etc.
[0027] Preferably, if the surface of the electrolyte substrate is coated with the cathode slurry, the temperature of the fourth sintering stage is 1000-1100°C, for example, 1000°C, 1010°C, 1020°C, 1030°C, 1040°C, 1050°C, 1060°C, 1070°C, 1080°C, 1090°C or 1100°C, etc.
[0028] Preferably, the heating rate of the fourth stage sintering is 0.5-1°C / min, for example, 0.5°C / min, 0.6°C / min, 0.7°C / min, 0.8°C / min, 0.9°C / min or 1°C / min.
[0029] Preferably, the holding time of the fourth stage sintering is 120 to 240 min, for example, 120 min, 140 min, 160 min, 180 min, 200 min, 220 min, 240 min, etc.
[0030] As a preferred technical solution of the present invention, the anode slurry includes a first binder, a first pore former and a composite oxide anode powder.
[0031] Preferably, the method for preparing the anode slurry comprises the following steps: mixing a first binder, a first pore former and a composite oxide anode powder to obtain the anode slurry.
[0032] Preferably, the mixing comprises hand grinding or ball milling.
[0033] Preferably, after the mixing, defoaming is also included.
[0034] Preferably, the debubbling comprises ultrasonic debubbling.
[0035] Preferably, the defoaming time is 15 to 45 minutes, for example, 15 minutes, 20 minutes, 25 minutes, 30 minutes, 35 minutes, 40 minutes or 45 minutes.
[0036] Preferably, based on the mass of the composite oxide anode powder, the added amount of the first pore-forming agent is 3 to 15wt%, for example, 3wt%, 4wt%, 5wt%, 6wt%, 7wt%, 8wt%, 9wt%, 10wt%, 11wt%, 12wt%, 13wt%, 14wt% or 15wt%, etc.
[0037] Preferably, the cathode slurry comprises a second binder, a second pore former and cathode powder.
[0038] Preferably, the method for preparing the cathode slurry comprises the following steps: mixing a second binder, a second pore-forming agent and a cathode powder to obtain the cathode slurry.
[0039] Preferably, the mixing comprises hand grinding or ball milling.
[0040] Preferably, after the mixing, defoaming is also included.
[0041] Preferably, the debubbling comprises ultrasonic debubbling.
[0042] Preferably, the defoaming time is 15 to 45 minutes, for example, 15 minutes, 20 minutes, 25 minutes, 30 minutes, 35 minutes, 40 minutes or 45 minutes.
[0043] Preferably, based on the mass of the cathode powder, the added amount of the second pore-forming agent is 2-10wt%, for example, 2wt%, 3wt%, 4wt%, 5wt%, 6wt%, 7wt%, 8wt%, 9wt% or 10wt%.
[0044] As a preferred technical solution of the present invention, the first pore former and the second pore former each independently include a spherical pore former and a special-shaped pore former.
[0045] Preferably, the spherical pore former comprises polymethyl methacrylate or polystyrene microspheres.
[0046] Preferably, the special-shaped pore-forming agent includes any one of carbon powder, graphite or starch, or a combination of at least two of them.
[0047] The present invention adds spherical pore formers and special-shaped pore formers together to enrich the generation of three-phase interfaces, has a certain inhibitory effect on defects, prevents the generation of large defects in anode materials and cathode materials, and can also ensure a loose pore structure. The place where the electrochemical reaction occurs is at the three-phase interface (TPB), and TPB is defined as the collective position where the oxygen ion conductor, the electronic conductive metal phase and the gas phase converge. If the connection of any of the three phases is disconnected, the reaction will not be able to proceed. For example, if ions from the electrolyte cannot reach the reaction position, or gas-phase fuel molecules cannot reach the reaction position, or electrons cannot move out of the reaction position, then the electrochemical reaction will not occur, wherein the size of the TPB is largely affected by the material structure and components.
[0048] Preferably, the particle sizes of the spherical pore formers and the irregular pore formers are independently 1 to 8 μm, for example, 1 μm, 2 μm, 3 μm, 4 μm, 5 μm, 6 μm, 7 μm or 8 μm.
[0049] Preferably, the mass ratio of the spherical pore former to the irregular pore former is (1-3):1, such as 1:1, 1.5:1, 2:1, 2.5:1 or 3:1.
[0050] Preferably, the first binder and the second binder each independently comprise terpineol.
[0051] Preferably, the first binder and the second binder further independently include polyvinyl butyral and / or ethyl cellulose.
[0052] The present invention adopts a combination of pineol and polyvinyl butyral, or a combination of pineol and ethyl cellulose, or a combination of pineol, polyvinyl butyral and ethyl cellulose as a binder, which can adjust the viscosity of the slurry within a certain range to adapt to molding while having a certain pore-forming function. Compared with the common binders in solid oxide fuel cells, it has the advantage of flexible experiments.
[0053] Preferably, the mass ratio of pineol, polyvinyl butyral and ethyl cellulose is (5-15):(0-2):(0-3), and not all of them are 0 at the same time, for example, 5:1:1, 8:1:2, 10:1:3, 12:1:0, 15:1:1, 10:1:0, 8:0:2, 12:0:3 or 15:2:3, etc.
[0054] Preferably, the mass ratio of the first binder to the composite oxide anode powder is m:n, m+n=10, 4≤m≤6, for example, m may be 4, 4.5, 5, 5.5 or 6.
[0055] Preferably, the mass ratio of the second binder to the cathode powder is a:b, a+b=10, 4≤a≤6, for example, a may be 4, 4.5, 5, 5.5 or 6.
[0056] Preferably, the coating is followed by drying.
[0057] Preferably, the drying temperature is 50-90°C, for example, 50°C, 60°C, 70°C, 80°C or 90°C.
[0058] Preferably, the drying time is 6 to 16 hours, for example, 6 hours, 7 hours, 8 hours, 9 hours, 10 hours, 11 hours, 12 hours, 13 hours, 14 hours, 15 hours or 16 hours.
[0059] Preferably, when the anode slurry is coated, the coating thickness is 15 to 100 μm, for example, 15 μm, 25 μm, 35 μm, 45 μm, 55 μm, 65 μm, 75 μm, 85 μm, 95 μm or 100 μm.
[0060] Preferably, when the cathode slurry is coated, the coating thickness is 25 to 90 μm, for example, 25 μm, 35 μm, 45 μm, 55 μm, 65 μm, 75 μm, 85 μm or 90 μm.
[0061] Preferably, the coating comprises any one of screen printing, spraying or cross-brush coating.
[0062] As a preferred technical solution of the present invention, the method for preparing the composite oxide anode powder comprises the following steps:
[0063] The mixed metal solution is mixed with the precipitant solution to perform a coprecipitation reaction to obtain a precursor powder, which is then calcined to obtain a composite oxide anode powder;
[0064] The mixed metal solution comprises a doped rare earth source, a yttrium source, a zirconium source, a nickel source and a solvent.
[0065] In the present invention, raw materials of composite oxide anode powder are mixed together, and powders with uniform composition are prepared simultaneously by coprecipitation method, and doped rare earth elements can be completely dissolved in YSZ, thereby realizing uniform mixing of various components in composite oxide anode powder. Compared with the solid phase method, the coprecipitation method can realize atomic-level mixing of electrode material components in the precursor solution, and the formed precipitation product has uniform composition, thus avoiding the problem of uneven mixing of stirring and grinding components in the solid phase method, and the occurrence of NiO and YSZ phase aggregation, and the particle size of the particles prepared by the coprecipitation method is smaller, which reduces the subsequent grinding intensity.
[0066] As a preferred technical solution of the present invention, the doped rare earth source includes any one of rare earth nitrates, rare earth sulfates or rare earth chlorides, or a combination of at least two of them.
[0067] Preferably, the doped rare earth element in the doped rare earth source includes any one of Ce, Sm, Nd, La, Yb or Gd, or a combination of at least two of them.
[0068] Preferably, the doped rare earth element in the doped rare earth source includes a combination of at least two of Ce, Sm, Nd, La, Yb or Gd.
[0069] Preferably, the yttrium source comprises a yttrium salt and / or a hydrate of a yttrium salt.
[0070] Preferably, the yttrium source includes any one of Y(NO3)3·6H2O, Y2(SO4)3·8H2O or YCl3·6H2O, or a combination of at least two thereof.
[0071] Preferably, the zirconium source comprises a zirconium salt and / or a hydrate of a zirconium salt.
[0072] Preferably, the zirconium source includes any one of ZrOCl2·8H2O, ZrCl4 or Zr(NO3)4, or a combination of at least two thereof.
[0073] Preferably, the nickel source comprises a nickel salt and / or a hydrate of a nickel salt.
[0074] Preferably, the nickel source includes Ni(NO3)2·6H2O or NiSO4·6H2O.
[0075] Preferably, in the mixed metal solution, the molar ratio of zirconium element, yttrium element and doped rare earth element is 92:(10-24):(2-8), for example, 92:16:2, 92:16:3, 92:16:4, 92:16:5, 92:16:6, 92:16:7, 92:16:8, 92:10:2, 92:10:5, 92:10:8, 92:24:2, 92:24:5 or 92:24:8, etc.
[0076] Preferably, in the mixed metal solution, the total molar ratio of nickel to zirconium, yttrium and doped rare earth element is x:y, x+y=10, 4≤x≤6, for example, x can be 4, 4.5, 5, 5.5 or 6.
[0077] Preferably, the solvent comprises deionized water.
[0078] Preferably, the method for preparing the mixed metal solution comprises the following steps: uniformly mixing a doped rare earth source, a yttrium source, a zirconium source, a nickel source and a solvent under stirring and heating conditions to obtain the mixed metal solution.
[0079] Preferably, the stirring speed is 200-800 r / min, for example, 200 r / min, 300 r / min, 400 r / min, 500 r / min, 600 r / min, 700 r / min or 800 r / min.
[0080] Preferably, the heating temperature is 50-100°C, for example, 50°C, 60°C, 70°C, 80°C, 90°C or 100°C.
[0081] Preferably, the heating time is 1 to 5 hours, such as 1 hour, 2 hours, 3 hours, 4 hours or 5 hours.
[0082] Preferably, after the heating is completed, stirring is continued until the mixture is cooled to room temperature to obtain a mixed metal solution.
[0083] As a preferred technical solution of the present invention, the precipitant solution includes any one of a strong alkaline solution, a weak alkaline solution or a buffer solution, or a combination of at least two of them.
[0084] Preferably, the mass concentration of the precipitant solution is 0.5-3.0 mol / L, for example, 0.5 mol / L, 0.8 mol / L, 1.0 mol / L, 2.5 mol / L or 3.0 mol / L.
[0085] Preferably, the pH of the precipitant solution is ≥ 12, such as 12, 12.5, 13, 13.5 or 14.
[0086] Preferably, the mixing comprises: dropping the mixed metal solution into the precipitant solution.
[0087] Preferably, the dropping rate is 20-35 mL / min, for example, 20 mL / min, 22 mL / min, 24 mL / min, 26 mL / min, 28 mL / min, 30 mL / min, 32 mL / min or 35 mL / min.
[0088] Preferably, the coprecipitation reaction temperature is 30-40°C, for example, 30°C, 32°C, 34°C, 36°C, 38°C or 40°C.
[0089] Preferably, the stirring rate of the coprecipitation reaction is 300-500 r / min, for example, 300 r / min, 350 r / min, 400 r / min, 450 r / min or 500 r / min.
[0090] Preferably, when the pH of the mixed solution after dropwise addition is 7 to 8.5, the addition is stopped. For example, the pH may be 7, 7.2, 7.5, 7.8, 8.0, 8.2 or 8.5.
[0091] Preferably, after the coprecipitation reaction is completed, solid-liquid separation, washing, drying and screening are sequentially performed.
[0092] Preferably, the solid-liquid separation comprises any one of suction filtration, rotary evaporation or centrifugation.
[0093] Preferably, the washing comprises washing with deionized water and anhydrous ethanol for 2 to 5 times, for example, 2 times, 3 times, 4 times or 5 times.
[0094] Preferably, the drying temperature is 60-100°C, for example, 60°C, 65°C, 70°C, 75°C, 80°C, 85°C, 90°C, 95°C or 100°C.
[0095] Preferably, the drying time is 8.8 to 15.8 h, for example, 8.8 h, 9 h, 9.5 h, 10 h, 10.5 h, 11 h, 11.5 h, 12 h, 12.5 h, 13 h, 13.5 h, 14 h, 14.5 h, 15 h or 15.8 h.
[0096] Preferably, the mesh size of the sieving is between 180 and 400 meshes, such as 180 mesh, 200 mesh, 250 mesh, 300 mesh, 350 mesh or 400 mesh.
[0097] Preferably, the calcination temperature is 900-1300°C, for example, 900°C, 1000°C, 1100°C, 1200°C or 1300°C.
[0098] Preferably, the heating rate of the calcination is 5 to 8°C / min, such as 5°C / min, 6°C / min, 7°C / min or 8°C / min.
[0099] Preferably, the calcination holding time is 2 to 4 hours, such as 2 hours, 3 hours or 4 hours.
[0100] As a preferred technical solution of the present invention, the preparation method comprises the following steps:
[0101] The first electrode slurry is applied to one side of the electrolyte substrate, dried at 50-90° C. for 6-16 hours, and sintered once to obtain an electrode half-cell; the second electrode slurry is applied to the other side of the electrolyte substrate in the electrode half-cell, dried at 50-90° C. for 6-16 hours, and sintered twice to obtain a solid oxide fuel cell;
[0102] Wherein, the first electrode slurry includes anode slurry, and the second electrode slurry includes cathode slurry; or, the first electrode slurry includes cathode slurry, and the second electrode slurry includes anode slurry; the anode slurry includes a first binder, a first pore former and a composite oxide anode powder; based on the mass of the composite oxide anode powder, the addition amount of the first pore former is 3 to 15wt%; the cathode slurry includes a second binder, a second pore former and cathode powder; based on the mass of the cathode powder, the addition amount of the second pore former is 2 to 10wt%; the first pore former and the second pore former each independently include a spherical pore former and a shaped pore former; the spherical pore former The invention comprises polymethyl methacrylate or polystyrene microspheres; the special-shaped pore former comprises any one of carbon powder, graphite or starch or a combination of at least two thereof; the particle sizes of the spherical pore former and the special-shaped pore former are independently 1 to 8 μm; the mass ratio of the spherical pore former and the special-shaped pore former is (1 to 3):1; the first binder and the second binder independently comprise pine alcohol; the first binder and the second binder also independently comprise polyvinyl butyral and / or ethyl cellulose; the mass ratio of pine alcohol, polyvinyl butyral and ethyl cellulose is (5 to 15):(0 to 2):(0 to 3), and is not 0 at the same time; the first binder and the composite The mass ratio of the oxide anode powder is m:n, m+n=10, 4≤m≤6; the mass ratio of the second binder to the cathode powder is a:b, a+b=10, 4≤a≤6; when the anode slurry is applied, the coating thickness is 15-100 μm; when the cathode slurry is applied, the coating thickness is 25-90 μm; the coating includes any one of screen printing, spraying or cross brushing; the primary sintering and the secondary sintering each independently include a first sintering stage, a second sintering stage, a third sintering stage and a fourth sintering stage; the temperature of the first sintering stage is 150-300°C, the heating rate is 0.2-1°C / min, and the holding time is 60-120 min; the second stage sintering temperature is 400-600°C, the heating rate is 0.8-2°C / min, and the holding time is 120-240min; the third stage sintering temperature is 800-950°C, the heating rate is 1-2°C / min, and the holding time is 120-240min; if the surface of the electrolyte substrate is coated with the anode slurry, the fourth stage sintering temperature is 1250-1350°C; if the surface of the electrolyte substrate is coated with the cathode slurry, the fourth stage sintering temperature is 1000-1100°C; the heating rate of the fourth stage sintering is 0.5-1°C / min, and the holding time is 120-240min;
[0103] The preparation method of the composite oxide anode powder comprises the following steps: heating a doped rare earth source, a yttrium source, a zirconium source, a nickel source and a solvent at 200-800 r / min and 50-100° C. for 1-5 h, continuing stirring until cooling to room temperature to obtain a mixed metal solution, dripping the solution into a precipitant solution with a pH value of ≥12 at a rate of 20-35 mL / min to perform a coprecipitation reaction, controlling the temperature of the coprecipitation reaction at 30-40° C. and the stirring rate at 300-500 r / min, stopping the feeding when the pH value of the mixed solution after dripping is 7-8.5, continuing the reaction for 0.5-1 h, separating the solid from the liquid, washing with deionized water and anhydrous ethanol for 2-5 times respectively, drying at 60-100° C. for 8.8-15.8 h, crushing and sieving with a 180-400 mesh sieve to obtain a precursor powder, and calcining at a heating rate of 5-8° C. / min at 900-1300° C. for 2-4 h to obtain a composite oxide anode powder;
[0104] Wherein, the doped rare earth source includes any one of rare earth nitrates, rare earth sulfates or rare earth chlorides or a combination of at least two thereof; the rare earth element in the doped rare earth source includes any one of Ce, Sm, Nd, La, Yb or Gd or a combination of at least two thereof; the yttrium source includes yttrium salts and / or hydrates of yttrium salts; the yttrium source includes any one of Y(NO3)3·6H2O, Y2(CO3)3 or YCl3·6H2O or a combination of at least two thereof; the zirconium source includes zirconium salts and / or hydrates of zirconium salts; the zirconium source includes any one of ZrOCl2·8H2O, ZrCl4 or Zr(NO3)4 or a combination of at least two thereof; the nickel source Including nickel salt and / or nickel salt hydrate; the nickel source includes Ni(NO3)2·6H2O or NiSO4·6H2O; in the mixed metal solution, the molar ratio of zirconium element, yttrium element and doped rare earth element is 92:(10-24):(2-8); in the mixed metal solution, the total molar ratio of nickel element to zirconium element, yttrium element and doped rare earth element is x:y, x+y=10, 4≤x≤6; the precipitant solution includes any one of strong alkaline solution, weak alkaline solution or buffer solution or a combination of at least two of them; the mass concentration of the precipitant solution is 0.5-3.0 mol / L; the solid-liquid separation includes any one of suction filtration, rotary evaporation or centrifugation.
[0105] In a second aspect, the present invention further provides a solid oxide fuel cell, which is prepared according to the preparation method described in the first aspect.
[0106] Compared with the prior art, the present invention has at least the following beneficial effects:
[0107] 1) The present invention simplifies the existing solid oxide fuel cell sintering process through step-type sintering, optimizes the debinding process, shortens the sintering time, and reduces the warpage of the electrolyte-supported solid oxide fuel cell, so that the material is not easy to break during the battery test;
[0108] 2) The preparation process of the present invention has the advantages of short process, low production cost and high efficiency, and the prepared battery has many reaction active sites and better electrochemical performance;
[0109] 3) The present invention realizes uniform mixing of the components in the composite oxide anode powder through co-precipitation method, and can realize atomic-level mixing of the electrode material components in the precursor solution. The formed precipitation product has uniform composition, and the doped rare earth elements can be completely dissolved in YSZ. At the same time, the particles prepared by the co-precipitation method have smaller particle size, which reduces the subsequent grinding intensity. BRIEF DESCRIPTION OF THE DRAWINGS
[0110] Figure 1 A schematic diagram of the process for preparing a solid oxide fuel cell according to the present invention;
[0111] Figure 2 This is a schematic diagram of the process for preparing composite oxide anode powder according to the present invention;
[0112] Figure 3 This is a scanning electron microscope image of the composite oxide anode powder prepared in Example 1 of the present invention;
[0113] Figure 4 This is a scanning electron microscope image of the anode surface of the anode half-cell prepared in Example 1 of the present invention;
[0114] Figure 5 This is a scanning electron microscope image of the cathode surface in the solid oxide fuel cell prepared in Example 1 of the present invention;
[0115] Figure 6 This is a cross-sectional scanning electron microscope image of the solid oxide fuel cell prepared in Example 1 of the present invention;
[0116] Figure 7 The XRD diagrams of the composite oxide anode powders prepared in Examples 1 to 3 and Comparative Example 2 of the present invention are shown. DETAILED DESCRIPTION
[0117] The technical solution of the present invention is further described below in conjunction with the accompanying drawings and through specific implementation methods. However, the following examples are only simplified examples of the present invention and do not represent or limit the scope of protection of the present invention. The scope of protection of the present invention shall be subject to the claims.
[0118] Unless otherwise specified, the raw materials and reagents used in the following examples are commercially available or can be prepared by known methods.
[0119] The method for preparing the electrolyte substrate used in the specific embodiment of the present invention comprises the following steps:
[0120] Yttria and zirconium oxide powders are weighed according to a molar ratio of 92:8, ball-milled and hot-pressed and sintered at 1400-1600° C. for 6-12 hours to obtain an electrolyte blank, which is then cut, ground and polished to obtain an electrolyte substrate with a thickness of 150 μm to 300 μm.
[0121] The present invention provides a method for preparing a solid oxide fuel cell, the flow diagram of which is as follows: Figure 1 As shown, the preparation method comprises the following steps:
[0122] Applying a first electrode slurry to one side of the electrolyte substrate, sintering once to obtain an electrode half-cell, applying a second electrode slurry to the other side of the electrolyte substrate in the electrode half-cell, sintering twice to obtain a solid oxide fuel cell;
[0123] Wherein, the first electrode slurry includes anode slurry, and the second electrode slurry includes cathode slurry;
[0124] Alternatively, the first electrode slurry comprises a cathode slurry, and the second electrode slurry comprises an anode slurry.
[0125] The present invention also provides a method for preparing a composite oxide anode powder, the schematic diagram of the process is as follows Figure 2 As shown, the method comprises the following steps:
[0126] The mixed metal solution is mixed with the precipitant solution to perform a coprecipitation reaction to obtain a precursor powder, which is then calcined to obtain a composite oxide anode powder;
[0127] The mixed metal solution comprises a doped rare earth source, a yttrium source, a zirconium source, a nickel source and a solvent.
[0128] Example 1
[0129] This embodiment provides a method for preparing a solid oxide fuel cell, the method comprising the following steps:
[0130] The first binder is prepared by mixing pine alcohol and polyvinyl butyral in a mass ratio of 8:1, the binder and NiO-SYSZ composite oxide anode powder are weighed in a mass ratio of 6:4, polymethyl methacrylate with a particle size of 1.8 μm and carbon powder with a particle size of 6 μm are weighed according to 5wt% of the NiO-SYSZ composite oxide anode powder (the mass ratio of polymethyl methacrylate to carbon powder is 1:1), the above raw materials are evenly ground, and ultrasonic defoaming is performed for 20 minutes to obtain an anode slurry;
[0131] A second binder is prepared by mixing pine alcohol and polyvinyl butyral in a mass ratio of 8:1, the binder and cathode powder (GDC powder and LSCF powder) are weighed in a mass ratio of 6:4, polymethyl methacrylate with a particle size of 1.8 μm and carbon powder with a particle size of 6 μm are weighed according to 5wt% of the cathode powder (the mass ratio of polymethyl methacrylate to carbon powder is 1:1), the above raw materials are ground evenly, and ultrasonic defoaming is performed for 20 minutes to obtain GDC slurry, a mixed slurry with a mass ratio of LSCF to GDC of 6:4, and LSCF slurry;
[0132] The anode slurry was coated on one side of an electrolyte substrate with a thickness of 200 μm by a cross-brush method, with a coating thickness of 60 μm. After drying at 60°C for 12 h, the temperature was first increased to 200°C at a heating rate of 0.2°C / min, and kept warm for 60 min. The temperature was then increased to 400°C at a heating rate of 0.8°C / min, and kept warm for 120 min. The temperature was then increased to 900°C at a heating rate of 2°C / min, and kept warm for 120 min. The temperature was then increased to 1300°C at a heating rate of 1°C / min, and kept warm for 120 min to obtain an anode half-cell.
[0133] GDC slurry, a mixed slurry with a mass ratio of LSCF to GDC of 6:4, and LSCF slurry are sequentially coated on the other side surface of the electrolyte substrate in the anode half-cell by a cross brushing method to obtain a three-layer structure with a total coating thickness of 60 μm. After drying at 60° C. for 12 h, the temperature is first increased to 200° C. at a heating rate of 0.3° C. / min, and kept warm for 60 min. The temperature is then increased to 400° C. at a heating rate of 1° C. / min, and kept warm for 120 min. The temperature is then increased to 900° C. at a heating rate of 2° C. / min, and kept warm for 120 min. The temperature is then increased to 1050° C. at a heating rate of 1° C. / min, and kept warm for 120 min. A solid oxide fuel cell with a structure of NiO-SYSZ|YSZ|GDC|LSCF-GDC|LSCF is obtained.
[0134] The method for preparing the NiO-SYSZ composite oxide anode powder comprises the following steps:
[0135] According to the molar ratio of zirconium, yttrium and samarium in the mixed metal solution of 92:16:5, and the molar ratio of nickel to the total of zirconium, yttrium and samarium of 6:4, ZrOCl2·8H2O, Y(NO3)3·6H2O, Ni(NO3)2·6H2O and Sm(NO3)3·6H2O of corresponding masses are weighed, Ni(NO3)2·6H2O and deionized water are stirred at 400 r / min for 40 min to dissolve, ZrOCl2·8H2O, Y(NO3)3·6H2O, Sm(NO3)3·6H2O and deionized water are stirred at 360 r / min for 40 min to dissolve, and then added to the aqueous solution of Ni(NO3)2·6H2O, and stirred at 70°C and 500 r / min for 2 h to mix evenly, and continued to stir and cool to room temperature to obtain a mixed metal solution;
[0136] The mixed metal solution was added dropwise to a NaOH solution with a pH of 13.5 at a rate of 25 mL / min to carry out a coprecipitation reaction. The temperature of the coprecipitation reaction was controlled at 35° C. and the stirring rate was controlled at 500 r / min. When the pH of the mixed solution after the addition was 7.5, the addition was stopped. The reaction was continued for 0.5 h and then allowed to stand. The mixture was filtered. During the filtration process, deionized water and anhydrous ethanol were used to rinse the mixture twice respectively. The mixture was dried at 75° C. for 14 h, ground and sieved through a 200-mesh sieve to obtain a precursor powder. The precursor powder was calcined at 1200° C. for 2 h at a heating rate of 5° C. / min to obtain a NiO-SYSZ composite oxide anode powder.
[0137] Figure 3 The scanning electron microscope image of the composite oxide anode powder prepared in Example 1 is shown. It can be seen from the figure that the powder has a uniform morphology, is at the nanoscale level, has a smaller size distribution, and the distribution of the two phases is more uniform.
[0138] Figure 4 The scanning electron microscope image of the anode surface of the anode half-cell prepared in Example 1 is shown. It can be seen from the image that the surface of the anode electrode is loose and porous, ensuring sufficient three-phase interface for the anode reaction to occur.
[0139] Figure 5 The scanning electron microscope image of the cathode surface in the solid oxide fuel cell prepared in Example 1 is shown. It can be seen from the image that the cathode electrode surface is loose and porous, ensuring sufficient three-phase interface for cathode reaction to occur.
[0140] Figure 6 A cross-sectional scanning electron microscope image of the solid oxide fuel cell prepared in Example 1 is shown. As can be seen from the image, the middle is a dense electrolyte substrate, the left side is a loose and porous anode material, and the right side is a stacked cathode material, which is still loose and porous. The electrolyte substrate, anode material and cathode material are tightly bonded.
[0141] Example 2
[0142] This embodiment provides a method for preparing a solid oxide fuel cell, the method comprising the following steps:
[0143] The first binder is prepared by mixing pine alcohol and polyvinyl butyral in a mass ratio of 6:1, the binder and NiO-CYSZ composite oxide anode powder are weighed in a mass ratio of 4:6, polymethyl methacrylate with a particle size of 5 μm and carbon powder with a particle size of 1 μm are weighed according to 10wt% of the NiO-CYSZ composite oxide anode powder (the mass ratio of polymethyl methacrylate to carbon powder is 1:1), the above raw materials are evenly ground, and ultrasonic defoaming is performed for 15 minutes to obtain an anode slurry;
[0144] A second binder is prepared by mixing pine alcohol and polyvinyl butyral in a mass ratio of 6:1, the binder and cathode powder (GDC powder and LSCF powder) are weighed in a mass ratio of 4:6, polymethyl methacrylate with a particle size of 5 μm and carbon powder with a particle size of 1 μm are weighed according to 2wt% of the cathode powder (the mass ratio of polymethyl methacrylate to carbon powder is 1:1), the above raw materials are ground evenly, and ultrasonic defoaming is performed for 20 minutes to obtain GDC slurry, a mixed slurry with a mass ratio of LSCF to GDC of 6:4, and LSCF slurry;
[0145] The anode slurry was coated on one side of an electrolyte substrate with a thickness of 200 μm by a cross-brush method, with a coating thickness of 60 μm. After drying at 65°C for 9 hours, the temperature was first increased to 300°C at a heating rate of 0.5°C / min, and kept warm for 120 minutes. The temperature was then increased to 500°C at a heating rate of 1.2°C / min, and kept warm for 180 minutes. The temperature was then increased to 950°C at a heating rate of 1.5°C / min, and kept warm for 180 minutes. The temperature was then increased to 1350°C at a heating rate of 1°C / min, and kept warm for 180 minutes to obtain an anode half-cell.
[0146] GDC slurry, a mixed slurry with a mass ratio of LSCF to GDC of 6:4, and LSCF slurry are sequentially coated on the other side surface of the electrolyte substrate in the anode half-cell by a cross brushing method to obtain a three-layer structure with a total coating thickness of 60 μm. After drying at 65° C. for 9 hours, the temperature is first increased to 300° C. at a heating rate of 0.5° C. / min, and kept warm for 120 minutes. The temperature is then increased to 500° C. at a heating rate of 1.2° C. / min, and kept warm for 180 minutes. The temperature is then increased to 950° C. at a heating rate of 1.5° C. / min, and kept warm for 180 minutes. The temperature is then increased to 1100° C. at a heating rate of 1° C. / min, and kept warm for 180 minutes to obtain a solid oxide fuel cell with a structure of NiO-CYSZ|YSZ|GDC|LSCF-GDC|LSCF.
[0147] The method for preparing the NiO-CYSZ composite oxide anode powder comprises the following steps:
[0148] According to the molar ratio of zirconium, yttrium and cerium in the mixed metal solution of 92:16:3, and the molar ratio of nickel to the total of zirconium, yttrium and cerium of 5:5, ZrOCl2·8H2O, Y(NO3)3·6H2O, Ni(NO3)2·6H2O and Ce(NO3)3·6H2O of corresponding masses were weighed, Ni(NO3)2·6H2O and deionized water were stirred at 420 r / min for 40 min to dissolve, ZrOCl2·8H2O, Y(NO3)3·6H2O, Ce(NO3)3·6H2O and deionized water were stirred at 350 r / min for 30 min to dissolve, and then added to the aqueous solution of Ni(NO3)2·6H2O, and stirred at 60°C and 500 r / min for 1.5 h to mix evenly, and continued stirring to cool to room temperature to obtain a mixed metal solution;
[0149] The mixed metal solution was added dropwise to an NH3·H2O solution with a pH value of 13.8 at a rate of 20 mL / min to carry out a coprecipitation reaction. The temperature of the coprecipitation reaction was controlled at 32° C. and the stirring rate was controlled at 500 r / min. When the pH value of the mixed solution after the addition was 7, the addition was stopped. The mixture was allowed to stand after the reaction was continued for 0.5 h and filtered. During the filtration process, the mixture was rinsed twice with deionized water and anhydrous ethanol respectively. The mixture was dried at 70° C. for 12 h, ground and sieved through a 200-mesh sieve to obtain a precursor powder. The precursor powder was calcined at 900° C. for 2 h at a heating rate of 5° C. / min to obtain a NiO-CYSZ composite oxide anode powder.
[0150] Example 3
[0151] This embodiment provides a method for preparing a solid oxide fuel cell, the method comprising the following steps:
[0152] A first binder is prepared by mixing pine alcohol, polyvinyl butyral and ethyl cellulose in a mass ratio of 10:1:1, the binder and NiO-SCYSZ composite oxide anode powder are weighed in a mass ratio of 5:5, polymethyl methacrylate with a particle size of 8 μm and carbon powder with a particle size of 5.5 μm are weighed according to 12 wt% of the NiO-SCYSZ composite oxide anode powder (the mass ratio of polymethyl methacrylate to carbon powder is 1:1), the raw materials are uniformly ground, and ultrasonic defoaming is performed for 45 minutes to obtain an anode slurry;
[0153] A second binder is prepared by mixing pine alcohol, polyvinyl butyral and ethyl cellulose in a mass ratio of 10:1:1, and the binder and cathode powder (GDC powder and LSCF powder) are weighed in a mass ratio of 5:5. Polymethyl methacrylate with a particle size of 8 μm and carbon powder with a particle size of 5.5 μm are weighed according to 10 wt% of the cathode powder (the mass ratio of polymethyl methacrylate to carbon powder is 1:1), and the above raw materials are ground uniformly, and ultrasonic defoaming is performed for 20 minutes to obtain GDC slurry, a mixed slurry with a mass ratio of LSCF to GDC of 6:4, and LSCF slurry;
[0154] GDC slurry, mixed slurry with a mass ratio of LSCF to GDC of 6:4, and LSCF slurry were sequentially coated on one side surface of an electrolyte substrate with a thickness of 200 μm by a cross brushing method to obtain a three-layer structure with a coating thickness of 60 μm. After drying at 60°C for 16 hours, the temperature was first increased to 150°C at a heating rate of 1°C / min, and kept warm for 120 minutes, then increased to 400°C at a heating rate of 2°C / min, and kept warm for 240 minutes, then increased to 800°C at a heating rate of 2°C / min, and kept warm for 240 minutes, and then increased to 1000°C at a heating rate of 1°C / min, and kept warm for 240 minutes to obtain a cathode half-cell;
[0155] The anode slurry was coated on the other side of the electrolyte substrate in the cathode half-cell by a cross-brush method, with a coating thickness of 60 μm. After drying at 60°C for 16 hours, the temperature was first increased to 150°C at a heating rate of 1°C / min, and kept warm for 60 minutes. The temperature was then increased to 400°C at a heating rate of 2°C / min, and kept warm for 240 minutes. The temperature was then increased to 800°C at a heating rate of 2°C / min, and kept warm for 240 minutes. The temperature was then increased to 1250°C at a heating rate of 1°C / min, and kept warm for 180 minutes to obtain a solid oxide fuel cell with a structure of NiO-SCYSZ|YSZ|GDC|LSCF-GDC|LSCF.
[0156] The method for preparing the NiO-SCYSZ composite oxide anode powder comprises the following steps:
[0157] According to the molar ratio of zirconium, yttrium, samarium and cerium in the mixed metal solution of 92:16:1.6:6.4, and the molar ratio of nickel to the total of zirconium, yttrium, samarium and cerium of 7:3, ZrOCl2·8H2O, Y(NO3)3·6H2O, Ni(NO3)2·6H2O, Sm(NO3)3·6H2O and Ce(NO3)3·6H2O were weighed, and Ni(NO3)2·6H2O and deionized water were added. Water was stirred at 350 r / min for 30 min to dissolve, ZrOCl2·8H2O, Y(NO3)3·6H2O, Sm(NO3)3·6H2O, Ce(NO3)3·6H2O and deionized water were stirred at 350 r / min for 30 min to dissolve, then added into the aqueous solution of Ni(NO3)2·6H2O, stirred at 500 r / min for 3 h at 60°C to mix evenly, and continued to stir and cool to room temperature to obtain a mixed metal solution;
[0158] The mixed metal solution is added dropwise to an NH3·H2O-NH4HCO3 solution with a pH of 13.2 at a rate of 30 mL / min to carry out a coprecipitation reaction. The temperature of the coprecipitation reaction is controlled at 38°C and the stirring rate is controlled at 500 r / min. When the pH of the mixed solution after the dropwise addition is 7.8, the addition is stopped. The reaction is continued for 0.5 h and then allowed to stand and filtered. During the filtration process, deionized water and anhydrous ethanol are used to rinse twice respectively. The product is dried at 100°C for 12 h, ground and sieved through a 200-mesh sieve to obtain a precursor powder, which is calcined at 1300°C for 2 h at a heating rate of 8°C / min to obtain a NiO-SCYSZ composite oxide anode powder.
[0159] Example 4
[0160] This application example provides a method for preparing a solid oxide fuel cell. The difference between the preparation method and Example 1 is that the binder used in step (4) and step (6) is polyvinylidene fluoride (PVDF) dissolved in dimethyl sulfoxide (DMSO), and the rest of the preparation method and parameters are consistent with Example 1.
[0161] Example 5
[0162] This embodiment provides a method for preparing a solid oxide fuel cell. The difference between the preparation method and Example 1 is that in the first sintering, the temperature of the fourth stage sintering is 1200° C., and the rest of the preparation method and parameters are consistent with Example 1.
[0163] Example 6
[0164] The present embodiment provides a method for preparing a solid oxide fuel cell. The difference between the preparation method and Example 1 is that in the first sintering, the temperature is directly increased to 1300°C at a heating rate of 1°C / min, and the total insulation time is 420 minutes. In the second sintering, the temperature is directly increased to 1050°C at a heating rate of 1°C / min, and the total insulation time is 420 minutes. The remaining preparation methods and parameters are consistent with Example 1.
[0165] Example 7
[0166] This embodiment provides a method for preparing a solid oxide fuel cell. The difference between the preparation method and Example 1 is that only carbon powder is used as a pore-forming agent in the anode slurry and the cathode slurry, and the rest of the preparation method and parameters are consistent with Example 1.
[0167] Example 8
[0168] This embodiment provides a method for preparing a solid oxide fuel cell. The difference between the preparation method and Example 1 is that only polymethyl methacrylate is used as a pore-forming agent in the anode slurry and the cathode slurry, and the rest of the preparation method and parameters are consistent with Example 1.
[0169] Example 9
[0170] The present embodiment provides a preparation method for a solid oxide fuel cell. The preparation method differs from that in Example 1 in that the first sintering and the first stage sintering in the second sintering are omitted. In the first sintering, the temperature is directly increased to 400°C at a heating rate of 0.8°C / min, kept warm for 180 minutes, and then the third and fourth stages of sintering are performed; in the second sintering, the temperature is directly increased to 400°C at a heating rate of 1°C / min, kept warm for 180 minutes, and then the third and fourth stages of sintering are performed. The rest of the preparation method and parameters are consistent with those in Example 1.
[0171] Comparative Example 1
[0172] The present comparative example provides a method for preparing a solid oxide fuel cell. The difference between the present comparative example and Example 1 is that the first electrode slurry and the second electrode slurry are simultaneously coated on both sides of an electrolyte substrate with a thickness of 200 μm, and after drying, the temperature is first increased to 150°C at a heating rate of 1°C / min, and kept warm for 120 min, then increased to 400°C at a heating rate of 2°C / min, and kept warm for 240 min, then increased to 800°C at a heating rate of 2°C / min, and kept warm for 240 min, then increased to 1050°C at a heating rate of 1°C / min, and kept warm for 240 min, then increased to 1300°C at a heating rate of 1°C / min, and kept warm for 240 min, to obtain a solid oxide fuel cell with a structure of NiO-SYSZ|YSZ|GDC|LSCF-GDC|LSCF, and the rest of the preparation method and parameters are consistent with Example 1.
[0173] Comparative Example 2
[0174] This comparative example provides a method for preparing a solid oxide fuel cell. The difference between this comparative example and Example 1 is that the composite oxide anode powder is NiO-YSZ, which is not doped with samarium. In the corresponding preparation method, the addition of the samarium source is omitted, and the remaining preparation methods and parameters are consistent with Example 1.
[0175] Figure 7 The XRD patterns of the composite oxide anode powders prepared in Examples 1 to 3 and Comparative Example 2 are shown. It can be seen from the figure that the composite oxide anode powders have high crystallinity and no other impurity peaks appear, indicating that the doped rare earth elements are all dissolved in the YSZ lattice.
[0176] Comparative Example 3
[0177] This comparative example provides a method for preparing a solid oxide fuel cell. The difference between this comparative example and Example 1 is that the method for preparing the NiO-SYSZ composite oxide anode powder comprises the following steps:
[0178] NiO, Sm2O3 and 8 mol% yttrium oxide YSZ powders were wet ball-milled at 1000 rpm for 5 h, wherein the mass ratio of NiO, Sm2O3 and 8 mol% yttrium oxide YSZ powders was 6:4, 10 wt% ethanol was added as a dispersant, the slurry after ball milling was dried at 70°C for 12 h, and after grinding, it was sieved through a 200 mesh sieve to obtain a precursor powder, which was calcined at 1200°C for 2 h at a heating rate of 5°C / min to obtain a NiO-SYSZ composite oxide anode powder with a mass ratio of NiO to SYSZ of 6:4; the rest of the preparation method and parameters were consistent with Example 1.
[0179] The prepared solid oxide fuel cell was performance tested by the four-electrode method. The button cell was placed on a nested alumina ceramic tube with the anode facing downward and the cathode facing upward, and sealed with high-temperature glue to prevent leakage of the anode fuel gas. The inner tube of the lower ceramic tube was covered with a platinum mesh and contacted with the anode support through a nickel foam current collector. The fuel gas (hydrogen) was transmitted to the anode side through the lower inner tube, and the reaction products were discharged outward through the gap between the lower inner and outer tubes. The upper ceramic tube was also covered with a platinum mesh and contacted with the cathode through a cathode contact material for current collection, and air (oxygen) was transmitted to the cathode side through the upper tube. Before the test, the temperature must be slowly raised to 200°C and kept warm for about 2 hours to solidify the high-temperature glue, and then 5 vol% H2 hydrogen-nitrogen mixed gas is introduced from the lower inner tube to protect the temperature, and then switched to pure H2 and kept warm at 750°C for 1.5 hours to reduce the anode NiO. After the open circuit voltage OCV remains stable, air is introduced through the upper tube to start the battery discharge test, obtain the battery IV performance curve, and calculate the corresponding power density. Based on this, the battery performance is evaluated. The specific test data is shown in Table 1.
[0180] Table 1
[0181] project <![CDATA[Maximum power density (mW·cm -2 )]]> Example 1 168.165 Example 2 150.186 Example 3 151.743 Example 4 122.557 Example 5 129.546 Example 6 121.116 Example 7 114.196 Example 8 116.453 Example 9 115.637 Comparative Example 1 108.332 Comparative Example 2 136.451 Comparative Example 3 83.529
[0182] The test results show that:
[0183] 1) It can be seen from Examples 1 to 7 that the preparation method of the solid oxide fuel cell provided by the present invention simplifies the sintering process, optimizes the debinding process, shortens the sintering time, and reduces the warpage of the electrolyte-supported solid oxide fuel cell through step-by-step sintering. The maximum power density of the solid oxide fuel cell is 114 mW·cm -2 The above further regulates the sintering process and the selection of raw materials, and the maximum power density is 150mW·cm -2 Above, the maximum can reach 168.165mW·cm -2 , and the battery structure of the present invention is universal, and the optimization of any electrode can bring similar effects;
[0184] 2) It can be seen from Examples 1 and 4 that in the preparation method of the present invention, pine alcohol and polyvinyl butyral are used as binders. Pinyl alcohol has a thickening effect. When used in combination with polyvinyl butyral, it can further improve the pore-forming ability during the electrode sintering and debinding process, making the pores in the anode and cathode forming process more uniform, thereby improving the maximum power density of the solid oxide fuel cell;
[0185] 3) It can be seen from Examples 1 and 5 that in the process of obtaining the anode half-cell by sintering once, the fourth stage sintering temperature is adjusted to 1250-1350° C., which can ensure that the anode phase grains are fully grown, thereby increasing the three-way bonding sites;
[0186] 4) It can be seen from Examples 1 and 6 that the present invention adopts a step-by-step sintering method, which matches four-stage sintering, first removes binder, then forms a pore structure, then promotes crystallization of particles, and then grows grains to form stable anode and cathode phases. If one-stage sintering is directly adopted, it will lead to insufficient grain development or excessive growth of single-phase aggregated grains, so that the electrical properties of the anode material and cathode material obtained after sintering are reduced, and the maximum power density is reduced;
[0187] 5) It can be seen from Examples 1, 7 and 8 that the present invention uses two pore formers in combination, wherein the spherical pore former polymethacrylic acid and the special-shaped pore former carbon powder are added together, which can enrich the generation of the three-phase interface, have a certain inhibitory effect on defects, prevent the generation of large defects in the anode material and the cathode material, and at the same time ensure a loose pore structure, thereby increasing the electrochemical reaction field and improving the maximum power density of the solid oxide fuel cell;
[0188] 6) It can be seen from Example 1 and Example 9 that the first stage of sintering in the primary sintering and the secondary sintering of the present invention is carried out under low temperature conditions, which can disperse the binder component in the anode slurry or the cathode slurry to the greatest extent, reduce the influence of the binder on the material, and fully remove the impurities and bubbles contained therein. If omitted, the binder and impurities will still exist, thereby affecting the formation of the pore structure in the anode and the cathode, and the stability of the assembled battery structure will be reduced;
[0189] 7) It can be seen from Example 1 and Comparative Example 1 that the present invention simultaneously applies the first electrode slurry and the second electrode slurry to both sides of the electrolyte substrate and sinters them at the same time. Although the anode and cathode materials will reach their respective sintering temperatures, the different properties of the slurries will still result in differences in their respective thermal expansion coefficients, and the warpage of the solid oxide fuel cell will increase, thereby reducing the maximum power density and stability of the solid oxide fuel cell.
[0190] 8) It can be seen from Example 1 and Comparative Example 2 that the composite oxide anode powder is doped with rare earth elements, which can be solid-dissolved with zirconium oxide in yttria-stabilized zirconium oxide, causing the lattice to be distorted and thus promoting ion transport in the electrochemical reaction. If the addition of rare earth elements is omitted, the electrochemical reaction rate will be reduced, thereby reducing the maximum power density of the solid oxide fuel cell;
[0191] 9) It can be seen from Example 1 and Comparative Example 3 that the present invention adopts the co-precipitation method to prepare the composite oxide anode powder. Compared with the traditional solid phase method, it can achieve uniform mixing of the components in the anode powder and prepare them together. The co-precipitation method can produce a powder with a smaller particle size. When used to prepare anode materials, it can make the distribution of each phase more uniform and greatly enrich the number of three-way bonding sites, thereby improving the maximum power density of solid oxide fuel cells.
[0192] In summary, the present invention provides a solid oxide fuel cell and a preparation method thereof. Through step-by-step sintering, the sintering process is simplified, the debinding process is optimized, the sintering time is shortened, and the warping of the electrolyte-supported solid oxide fuel cell is reduced, thereby solving the problem of easy breakage during the test process. At the same time, a composite oxide anode powder with uniform composition is prepared by co-precipitation, and the doped rare earth elements can be completely dissolved in YSZ, thereby achieving uniform mixing of the components in the composite oxide anode powder. The particles prepared by the co-precipitation method have a smaller particle size, thereby reducing the subsequent grinding intensity.
[0193] The applicant declares that the above is only a specific implementation mode of the present invention, but the protection scope of the present invention is not limited thereto. Those skilled in the art should understand that any changes or substitutions that can be easily thought of by those skilled in the art within the technical scope disclosed by the present invention shall fall within the protection scope and disclosure scope of the present invention.
Claims
1. A method for preparing a solid oxide fuel cell, characterized in that: The preparation method comprises the following steps: Applying a first electrode slurry to one side of the electrolyte substrate, sintering once to obtain an electrode half-cell, applying a second electrode slurry to the other side of the electrolyte substrate in the electrode half-cell, sintering twice to obtain a solid oxide fuel cell; Wherein, the first electrode slurry includes anode slurry, and the second electrode slurry includes cathode slurry; Alternatively, the first electrode slurry comprises a cathode slurry, and the second electrode slurry comprises an anode slurry.
2. The preparation method according to claim 1, characterized in that: The primary sintering and the secondary sintering each independently include a first stage sintering, a second stage sintering, a third stage sintering and a fourth stage sintering.
3. The preparation method according to claim 2, characterized in that: The temperature of the first stage sintering is 150-300°C; Preferably, the heating rate of the first stage sintering is 0.2-1°C / min; Preferably, the holding time of the first sintering stage is 60 to 120 minutes; Preferably, the temperature of the second sintering stage is 400-600°C; Preferably, the heating rate of the second stage sintering is 0.8-2°C / min; Preferably, the holding time of the second sintering stage is 120 to 240 minutes; Preferably, the temperature of the third stage sintering is 800-950°C; Preferably, the heating rate of the third stage sintering is 1-2°C / min; Preferably, the holding time of the third sintering stage is 120 to 240 minutes; Preferably, if the surface of the electrolyte substrate is coated with the anode slurry, the temperature of the fourth stage sintering is 1250-1350° C.; Preferably, if the surface of the electrolyte substrate is coated with the cathode slurry, the temperature of the fourth stage sintering is 1000-1100° C.; Preferably, the heating rate of the fourth stage sintering is 0.5-1°C / min; Preferably, the holding time of the fourth stage sintering is 120 to 240 minutes.
4. The preparation method according to any one of claims 1 to 3, characterized in that The anode slurry comprises a first binder, a first pore former and a composite oxide anode powder; Preferably, based on the mass of the composite oxide anode powder, the amount of the first pore former added is 3 to 15 wt %; Preferably, the cathode slurry comprises a second binder, a second pore former and cathode powder; Preferably, based on the mass of the cathode powder, the added amount of the second pore-forming agent is 2-10 wt %.
5. The preparation method according to claim 4, characterized in that: The first pore former and the second pore former each independently include a spherical pore former and a heteromorphic pore former; Preferably, the spherical pore former comprises polymethyl methacrylate or polystyrene microspheres; Preferably, the special-shaped pore-forming agent comprises any one of carbon powder, graphite or starch, or a combination of at least two thereof; Preferably, the particle sizes of the spherical pore former and the irregular pore former are independently 1 to 8 μm; Preferably, the mass ratio of the spherical pore former to the irregular pore former is (1-3):1; Preferably, the first binder and the second binder each independently comprise terpineol; Preferably, the first binder and the second binder further independently include polyvinyl butyral and / or ethyl cellulose; Preferably, the mass ratio of terpineol, polyvinyl butyral and ethyl cellulose is (5-15):(0-2):(0-3), and they are not 0 at the same time; Preferably, the mass ratio of the first binder to the composite oxide anode powder is m:n, m+n=10, 4≤m≤6; Preferably, the mass ratio of the second binder to the cathode powder is a:b, a+b=10, 4≤a≤6.
6. The preparation method according to claim 4, characterized in that: The method for preparing the composite oxide anode powder comprises the following steps: The mixed metal solution is mixed with the precipitant solution to perform a coprecipitation reaction to obtain a precursor powder, which is then calcined to obtain a composite oxide anode powder; The mixed metal solution comprises a doped rare earth source, a yttrium source, a zirconium source, a nickel source and a solvent.
7. The preparation method according to claim 6, characterized in that: The doped rare earth source includes any one of rare earth nitrates, rare earth sulfates or rare earth chlorides, or a combination of at least two thereof; Preferably, the doped rare earth element in the doped rare earth source includes any one or a combination of at least two of Ce, Sm, Nd, La, Yb or Gd; Preferably, the doped rare earth element in the doped rare earth source includes a combination of at least two of Ce, Sm, Nd, La, Yb or Gd; Preferably, the yttrium source comprises a yttrium salt and / or a hydrate of a yttrium salt; Preferably, the yttrium source includes any one of Y(NO3)3·6H2O, Y2(SO4)3·8H2O or YCl3·6H2O or a combination of at least two thereof; Preferably, the zirconium source comprises a zirconium salt and / or a hydrate of a zirconium salt; Preferably, the zirconium source includes any one or a combination of at least two of ZrOCl2·8H2O, ZrCl4 or Zr(NO3)4; Preferably, the nickel source comprises a nickel salt and / or a hydrate of a nickel salt; Preferably, the nickel source comprises Ni(NO3)2·6H2O or NiSO4·6H2O; Preferably, in the mixed metal solution, the molar ratio of zirconium element, yttrium element and doped rare earth element is 92:(10-24):(2-8); Preferably, in the mixed metal solution, the total molar ratio of nickel element to zirconium element, yttrium element and doped rare earth element is x:y, x+y=10, 4≤x≤6.
8. The preparation method according to claim 6 or 7, characterized in that: The precipitant solution includes any one of a strong base solution, a weak base solution or a buffer solution; Preferably, the pH of the precipitant solution is ≥12; Preferably, the mixing comprises: dropping the mixed metal solution into the precipitant solution; Preferably, the dripping rate is 20 to 35 mL / min; Preferably, the temperature of the coprecipitation reaction is 30-40°C; Preferably, when the pH of the mixed solution after the dropwise addition is 7 to 8.5, the addition is stopped; Preferably, the calcination temperature is 900-1300°C; Preferably, the heating rate of the calcination is 5 to 8°C / min; Preferably, the calcination holding time is 2 to 4 hours.
9. The preparation method according to claim 1, characterized in that: The preparation method comprises the following steps: The first electrode slurry is applied to one side of the electrolyte substrate, dried at 50-90° C. for 6-16 hours, and sintered once to obtain an electrode half-cell; the second electrode slurry is applied to the other side of the electrolyte substrate in the electrode half-cell, dried at 50-90° C. for 6-16 hours, and sintered twice to obtain a solid oxide fuel cell; Wherein, the first electrode slurry includes anode slurry, and the second electrode slurry includes cathode slurry; or, the first electrode slurry includes cathode slurry, and the second electrode slurry includes anode slurry; the anode slurry includes a first binder, a first pore former and a composite oxide anode powder; based on the mass of the composite oxide anode powder, the addition amount of the first pore former is 3 to 15wt%; the cathode slurry includes a second binder, a second pore former and cathode powder; based on the mass of the cathode powder, the addition amount of the second pore former is 2 to 10wt%; the first pore former and the second pore former each independently include a spherical pore former and a shaped pore former; the spherical pore former The invention comprises polymethyl methacrylate or polystyrene microspheres; the special-shaped pore former comprises any one of carbon powder, graphite or starch or a combination of at least two thereof; the particle sizes of the spherical pore former and the special-shaped pore former are independently 1 to 8 μm; the mass ratio of the spherical pore former and the special-shaped pore former is (1 to 3):1; the first binder and the second binder independently comprise pine alcohol; the first binder and the second binder also independently comprise polyvinyl butyral and / or ethyl cellulose; the mass ratio of pine alcohol, polyvinyl butyral and ethyl cellulose is (5 to 15):(0 to 2):(0 to 3), and is not 0 at the same time; the first binder and the composite The mass ratio of the oxide anode powder is m:n, m+n=10, 4≤m≤6; the mass ratio of the second binder to the cathode powder is a:b, a+b=10, 4≤a≤6; when the anode slurry is applied, the coating thickness is 15-100 μm; when the cathode slurry is applied, the coating thickness is 25-90 μm; the coating includes any one of screen printing, spraying or cross brushing; the primary sintering and the secondary sintering each independently include a first sintering stage, a second sintering stage, a third sintering stage and a fourth sintering stage; the temperature of the first sintering stage is 150-300°C, the heating rate is 0.2-1°C / min, and the holding time is 60-120 min; the second stage sintering temperature is 400-600°C, the heating rate is 0.8-2°C / min, and the holding time is 120-240min; the third stage sintering temperature is 800-950°C, the heating rate is 1-2°C / min, and the holding time is 120-240min; if the surface of the electrolyte substrate is coated with the anode slurry, the fourth stage sintering temperature is 1250-1350°C; if the surface of the electrolyte substrate is coated with the cathode slurry, the fourth stage sintering temperature is 1000-1100°C; the heating rate of the fourth stage sintering is 0.5-1°C / min, and the holding time is 120-240min; The preparation method of the composite oxide anode powder comprises the following steps: heating a doped rare earth source, a yttrium source, a zirconium source, a nickel source and a solvent at 200-800 r / min and 50-100° C. for 1-5 h, continuing stirring until cooling to room temperature to obtain a mixed metal solution, dripping the solution into a precipitant solution with a pH value of ≥12 at a rate of 20-35 mL / min to perform a coprecipitation reaction, controlling the temperature of the coprecipitation reaction at 30-40° C. and the stirring rate at 300-500 r / min, stopping the feeding when the pH value of the mixed solution after dripping is 7-8.5, continuing the reaction for 0.5-1 h, separating the solid from the liquid, washing with deionized water and anhydrous ethanol for 2-5 times respectively, drying at 60-100° C. for 8.8-15.8 h, crushing and sieving with a 180-400 mesh sieve to obtain a precursor powder, and calcining at a heating rate of 5-8° C. / min at 900-1300° C. for 2-4 h to obtain a composite oxide anode powder; Wherein, the doped rare earth source includes any one of rare earth nitrates, rare earth sulfates or rare earth chlorides or a combination of at least two thereof; the rare earth element in the doped rare earth source includes any one of Ce, Sm, Nd, La, Yb or Gd or a combination of at least two thereof; the yttrium source includes yttrium salts and / or hydrates of yttrium salts; the yttrium source includes any one of Y(NO3)3·6H2O, Y2(CO3)3 or YCl3·6H2O or a combination of at least two thereof; the zirconium source includes zirconium salts and / or hydrates of zirconium salts; the zirconium source includes any one of ZrOCl2·8H2O, ZrCl4 or Zr(NO3)4 or a combination of at least two thereof; the nickel source Including nickel salt and / or nickel salt hydrate; the nickel source includes Ni(NO3)2·6H2O or NiSO4·6H2O; in the mixed metal solution, the molar ratio of zirconium element, yttrium element and doped rare earth element is 92:(10-24):(2-8); in the mixed metal solution, the total molar ratio of nickel element to zirconium element, yttrium element and doped rare earth element is x:y, x+y=10, 4≤x≤6; the precipitant solution includes any one of strong alkaline solution, weak alkaline solution or buffer solution or a combination of at least two of them; the mass concentration of the precipitant solution is 0.5-3.0 mol / L; the solid-liquid separation includes any one of suction filtration, rotary evaporation or centrifugation.
10. A solid oxide fuel cell, characterized in that: The solid oxide fuel cell is prepared according to the preparation method according to any one of claims 1-9.